Deformability and geometry of neonatal erythrocytes with irregular shapes - Ruef, Peter; Linderkamp, Otwin (Pediatric research, 1999)
More stomatocytes, spherocytes, and erythrocytes with spicules and protrusions are found in blood from newborn infants than in blood from adults. The objective of this study was to measure volume, surface area, membrane rigidity, and viscosity of red blood cells (RBC) with irregular shapes in preterm and full-term neonates. RBC from 13 full-term and 12 preterm (25-36 wk of gestation) infants were studied by means of a micropipette system. In full-term neonates and in preterm infants, 19 and 26% of RBC, respectively, showed shapes different from those of discocytes. Keratocytes, spherocytes, akanthocytes (in full-term infants), and elliptocytes (in preterm infants) had smaller volumes than did discocytes (p < 0.05). Spherocytes showed decreased and elliptocytes had increased excess surface area and swelling capacity compared with discocytes, indicating both volume and membrane loss for spherocytes and only volume loss for elliptocytes. Immature RBC and knizocytes had similar large volumes and surface areas, suggesting that knizocytes in neonates are relatively young RBC. Increased membrane rigidity was found only in stomatocytes. Membrane viscosity was decreased in immature RBC and knizocytes and increased in stomatocytes, keratocytes, akanthocytes, and elliptocytes when compared with discocytes. There were inverse relationships between RBC volume and membrane rigidity (r = -0.42) and between RBC volume and membrane viscosity (r = -0.72). This suggests that volume loss of neonatal RBC is associated with impaired membrane deformability. Moreover, we conclude that the geometry and membrane deformability of some of the irregularly shaped neonatal RBC resemble properties of RBC in hemolytic anemias (e.g. spherocytosis).
Gesehen am 28.12.2020